Relative competitive ability of crabgrass in coexistence with flooded rice and soybean - Agostinetto, Dirceu; Fontana, Lisiane Camponogara; Vargas, Leandro; Markus, Catarine; de Oliveira, Ezequiel (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to compare the relative competitive ability of crabgrass with flooded rice and soybean crops. Five experiments were performed in the 2009/2010 and 2010/2011 seasons, in a completely randomized design with four replicates. The treatments consisted of plant proportions of crabgrass, flooded rice or soybean (at 100:0, 75:25, 50:50, 25:75 and 0:100%). Leaf area and shoot dry weight were evaluated at 45 days after emergence. The competition between crabgrass and flooded rice or soybean occurs for the same environment resources. Crabgrass plants have a lower individual competitive ability than flooded rice and soybean, when they occur in the same proportion of plants. When flooded rice or soybean are associated with crabgrass, the intraspecific competition dominates, while for the weed the interspecific competition prevails as the most harmful.